CONSTRUCTIVE AND DIMENSIONAL CONSIDERATIONS FOR THE CONSTRUCTION OF A VERTICAL TWO-PISTON INJECTION STAND (Nonconventional Technologies Review, 2024)
This article discusses dimensional and thermal analysis and types of heat dissipation on the surface of linear and vertical piston injection system parts. The injection parts of the components and the conditions necessary for the implementation of the simulation model using heat transfer phenomena are presented. Specifically, in the current study we will only use convection and radiation and heat conduction. It is also desired to analyze the evolution of temperatures according to the power that the resistor applies to the entire assembly. In this case, the materials used for the individual parts of the assembly are also very important, as they play an important role in heat transfer in terms of thermal conductivity.
Keywords: CAE part; thermal analysis; fabrication; simulation; thermal radiation